Conclusion: prospects for analysing committees in comparative perspective. Issue 3 (3rd July 2019) - Gaines, Brian J.; Goodwin, Mark; Bates, Stephen Holden; Sin, Gisela
ABSTRACT: While theories of committees in the U.S. Congress can continue to play a central role in the still-growing comparative study of committees, they require careful, frequent modification. Moreover, more fruitful study of committees may require a wider framework, recognising more fully that committees are institutions embedded in wider social structures.